PENGARUH GERAKAN LITERASI SEKOLAH DAN PENERAPAN KONSEP SEKOLAH RAMAH ANAK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM: (Penelitian pada Siswa Kelas V SDIT Miftahul Ulum Cinere, Depok) - Muazzikin Ripai (el-Moona: Jurnal Ilmu Pendidikan Islam, 2020)
They study aims to find the influence between the School Literacy Movement andthe application of the Child Friendly School concepts to student learning outcomes at the SDIT Miftahul Ulum. In this study, the authors have found theories to gain a deeper understanding of the definitions and concepts related to the concept of the School Literacy Movement,the application of the Child Friendly School concepts and student learning outcomes. Based on the problem formulation, we have found: 1) Is there positive and significant influence between the School Literacy Movement to the student learning outcomes? 2) Is there positive and significant influence between the application of the Child Friendly School concepts to the student learning outcomes? 3) Is there positive and significant influence between the School Literacy Movement andthe Application of the Child Friendly School Concepts together towards to the student learning outcomes? In this research, the researcher is using the method of survey with correlation technique and simple and multiple regression analaysis. Sample was used by using the Slovin formula, with 91 respondents at SDIT Miftahul Ulum Cinere Depok. Data collection techniques are using the sample questionnaires, tests, observations, documentation and interviews. Data analaysis techniques are using descriptive analaysis model, correlation coefficient, simple and multiple regression analaysis. The results of study show that First, there is positive and significant influence on the School Literacy Movement to the student learning outcomes at SDIT Miftahul Ulum Cinere Depok, it can be seen from the correlation coefficient of 0,772 (positive liner correlation close the value of +1 or positive 1) and the coefficient of determination R square of 59,6%, the simple regression equation shows values Ŷ =-14,603+0,803X1, for every improvement of the School Literacy Movement (one score) leads the student learning outcomes that is equal 0,803. Second; there is positive and significant influence on the application of the Child Friendly School concepts to the student learning outcomes at SDIT Miftahul Ulum Cinere Depok, it can be seen from the correlation coefficient of 0,450 (positive liner correlation close the value of +1 or positive 1) and the coefficient of determination R square of 45% the simple regression equation shows values Ŷ=-10,572+0,698X2, for every improvement of the application of the Child Friendly School concepts(one score) leads the student learning outcomes that is equal 0,698.Third; there is positive and significant impact on the School Literacy Movement and the application of the Child Friendly School concepts together to the student learning outcomes at SDIT Miftahul Ulum Cinere Depok, it can be seen from the correlation coefficient of 0,877 (positive liner correlation close the value of +1 or positive 1) and the coefficient of determination R square of 77% the simple regression equation shows values Ŷ=-55,672+ 0,632X1+0,476X2, for each improvement (one score) of the School Literacy Movement and the application of the Child Friendly School concepts jointly influencing the student learning outcomes for 1,108.